COMPUTATIONAL ANALYSIS OF THE MIXING ZONE IN THE COMBUSTION CHAMBER OF RAMJET - Adil A. Al-Hemiri; Sa’ad A. Fa’ek (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
A theoretical analysis of mixing in the secondary combustion chamber of ramjet is presented. Theoretical investigations were initiated to insight into the flow field of the mixing zone of the ramjet combustor and a computer program to calculate axisymmetric, reacting and inert flow was developed. The mathematical model of the mixing zone of ramjet comprises differential equations for: continuity, momentum, stagnation enthalpy, concentration, turbulence energy and its dissipation rate. The simultaneous solution of these equations by means of a finite-difference solution algorithm yields the values of the variable at all internal grid nodes. The results showed that increasing air mass flow (0.32 to 0.64 kg/s) increases the development of velocity profile due to the high turbulence generated resulting in very fast mixing and homogenous flow. And the occurrence of chemical reaction causes higher local temperature and composition resulting in faster development of the velocity profile